THE EFFECT OF TEAMS GAMES TOURNAMENT MODEL ON INDONESIAN LEARNING OUTCOMES IN CLASS V SDN 101 INPRES UJUNG MAROS - Hamzah, Rahma Ashari (JURNAL PENDIDIKAN DASAR NUSANTARA, 2022)
The Influence of Teams Games Tournament (TGT) Cooperative Learning Model on Indonesian Language Learning Outcomes for Fifth Grade Students of SDN 101 Inpres Ujung Maros Regency. This study aims to determine the description of the Teams Games Tournament learning model carried out in class V SDN 101 Inpres Ujung, Maros Regency and to determine the effect of the Teams Games Tournament learning model on Indonesian language learning outcomes for fifth grade students of SDN 101 Inpres Ujung, Maros Regency. This research is a quantitative research where the type of research is pre-experimental. The population and sample in this study were all fifth grade students of SDN 101 Inpres Ujung, Maros Regency as many as 22 people with the total sampling method (total sampling). The research instruments are 1) test guidelines (pretest and posttest), 2) interview guidelines, 3) documentation. The results showed that 1) the description of the learning process in class V SDN 101 Inpres Ujung Maros Regency using the Teams Games Tournament learning model went well and efficiently, before the learning activities started the students were grouped into several groups consisting of 5-6 students and there was feedback. good relationship between students and teachers. 2) there is an effect of implementing the Teams Games Tournament learning model on student learning outcomes seen from the Mean 54.55 to 85.91.